Strategiczny wymiar partnerstwa - Bembenek, Bogusław (Strategic meaning of partnership, 2006)
In the article the meaning of strategic partnership was presented. The author describes this type of partnership as a long term cooperation among partners which is built on principles of trust, risk and benefit-sharing. The cooperation also consists in joint investment and organizational undertakings, which contributes to reaching both the individual and team aims. It was stressed that the strategic partnership is an example of conscious and consistently realized for a long time conception to hold by the enterprise some solid competitive superiority on the market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 28-36